(untitled) (Bangladesh Journal of Botany, 2020)
Chemical composition, antioxidant and antibacterial activities of the essential oil of Curcuma phaeocaulis were analysed. In the aerial part, 22 compounds account for 69.23% of the total essential oil and authenticated, while in the underground part, 32 compounds account for 84.28% of the total essential oil and authenticated. Among the compounds detected, α-pinene, camphene, eucalyptol, camphor, borneol, β- tumerone, epi-curzerenone were the main compounds of volatile oil in both parts of Curcuma phaeocaulis. In addition, various lipid antioxidant properties by peroxidation assays, inoxidizability and antibacterial action were assessed. The result may be considered as a baseline study for the further development and application of Curcuma phaeocaulis.